Emerging Roles of Astrocytes in Neuro-Vascular Unit and the Tripartite Synapse With Emphasis on Reactive Gliosis in the Context of Alzheimer’s Disease - Liu, Cai-Yun; Yang, Yu; Ju, Wei-Na; Wang, Xu; Zhang, Hong-Liang (Frontiers in Cellular Neuroscience, 2018)
Astrocytes, which are fivefold more numerous than neurons in the central nervous system, are traditionally viewed to provide simple structural and nutritional supports for neurons and to participate in the composition of the blood brain barrier. In recent years, the active roles of astrocytes in regulating cerebral blood flow and in maintaining the homeostasis of the tripartite synapse have attracted increasing attention. More importantly, astrocytes have been associated with the pathogenesis of Alzheimer’s disease (AD), a major cause of dementia in the elderly. Although microglia-induced inflammation is considered important in the development and progression of AD, inflammation attributable to astrogliosis may also play crucial roles. A1 reactive astrocytes induced by inflammatory stimuli might be harmful by up-regulating several classical complement cascade genes thereby leading to chronic inflammation, while A2 induced by ischemia might be protective by up-regulating several neurotrophic factors. Here we provide a concise review of the emerging roles of astrocytes in the homeostasis maintenance of the neuro-vascular unit and the tripartite synapse with emphasis on reactive astrogliosis in the context of AD, so as to pave the way for further research in this area, and to search for potential therapeutic targets of AD.